Efektivitas Masase Effleurage dan Akupresur Sanyinjiao Point Terhadap Intensitas Nyeri Haid - Silfia Dewi; Fatma Sylvana Dewi Harahap; Aida Fitria (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Menstrual pain management measures or non-pharmacological therapy are alternative interventions or combinations in reducing the intensity of menstrual pain. Non-pharmacological therapy is a cheap, simple and safe therapy that uses physiological processes, one of which is massage effleurage and acupressure. The purpose of this study was to determine and analyze the effect of effleurage massage and Sanyinjiao point acupressure on the intensity of menstrual pain. The research design method used was a quasi-experimental pre-test and post-test two design. The sample used was 68 female students who experienced menstrual pain in both groups. The statistical test used was the Wilcoxon signed rank test and the Mann-Whitney test. In the Wilcoxon marked ranking test, the study of the effleurage massage group showed a p value = 0.000, then there was an effect after doing the effleurage massage, and the acupressure group showed a p value = 0.000, so there was an effect after applying acupressure on the menstrual pain scale. In conclusion, non-pharmacological therapy, massage effleurage and acupressure are effective in reducing the intensity of menstrual pain in female students. In the Mann-Whitney test, there are differences in the effect of effleurage massage and acupressure in overcoming menstrual pain, and the difference in the intensity of menstrual pain from the effect of effleurage massage is 44.09 greater than acupressure 24.91, p = 0.000. Acupressure is more effective than massage effleurage in dealing with menstrual pain, because acupressure therapy with a focus on the sanyinjiao point can increase endorphins levels and relieve pain more quickly.